2012
DOI: 10.1073/pnas.1207986110
|View full text |Cite
|
Sign up to set email alerts
|

CpG underrepresentation and the bacterial CpG-specific DNA methyltransferase M.MpeI

Abstract: Cytosine methylation promotes deamination. In eukaryotes, CpG methylation is thought to account for CpG underrepresentation. Whether scarcity of CpGs in prokaryotic genomes is diagnostic for methylation is not clear. Here, we report that Mycoplasms tend to be CpG depleted and to harbor a family of constitutively expressed or phase variable CpG-specific DNA methyltransferases. The very CpG poor Mycoplasma penetrans and its constitutively active CpGspecific methyltransferase M.MpeI were chosen for further charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 41 publications
6
70
0
1
Order By: Relevance
“…The best model structure was built using the template of Mycoplasma penetrans CpG-specific methyltransferase M. Mpel (Protein Data Bank entry: 4DKJ40) that shares over 90% sequence homology. The structure was visualized by using the programme PyMol (http://sourceforge.net/projects/pymol/).…”
Section: Methodsmentioning
confidence: 99%
“…The best model structure was built using the template of Mycoplasma penetrans CpG-specific methyltransferase M. Mpel (Protein Data Bank entry: 4DKJ40) that shares over 90% sequence homology. The structure was visualized by using the programme PyMol (http://sourceforge.net/projects/pymol/).…”
Section: Methodsmentioning
confidence: 99%
“…Direct comparison of these sequences with protein DNA complexes is not possible, since in all the crystals of protein-methylated DNA complexes the methylated nucleotide is flipped. [37][38][39] However, indirect readout or shape (topography) recognition is a well-known mechanism for DNA recognition. 40 This was further corroborated by Hansen et al, who showed that DNA shape is under evolutionary selection pressure.…”
Section: Considerations About the Methods Employedmentioning
confidence: 99%
“…codon usage bias); nonetheless we cannot rule out a role for mutational pressure. A recent report has documented CpG depletion in bacterial genomes [17]; this report also suggests a potential link between CpG-specific DNA methyltransferases encoded by bacteria and the loss of CpG dinucleotides. In addition, cytosine methylation in bacterial genomes has been associated with modulation of gene expression, motility, adhesion and virulence [18].…”
mentioning
confidence: 56%
“…As with eukaryotic genomes, methylation of CpGs in bacterial genomes has been linked to the depletion of CpGs [17]. If the depletion of CpG dinucleotides from the hypervirulent ribotypes of C.difficile is due to mutational pressure, we would expect that the loss of CpGs from the whole genome is more pronounced than that from the coding.…”
mentioning
confidence: 99%